2015
DOI: 10.1119/1.4908089
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does a Half-Kilogram of Water “Weigh”?

Abstract: Many educators have utilized the phenomenon of the so-called “hydrostatic paradox” to actively engage students in classroom instructional activities related to hydrostatic equilibrium.1 Various approaches requiring different levels of mathematical knowledge have been proposed in the literature to provide students clear explanations of this paradox.2 However, these attempts take for granted that students have already been taught and have internalized the concepts of force and pressure. The hydrostatic paradox i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In fluid mechanics, literature on teaching, formative assessment, remedial instruction, and tools are expanding much more than excepted. It has been reported that concepts from pressure and fluid statics [57,[60][61][62][63][64][65], to Archimedes' principle [66], to Bernoulli's law often lead to misunderstandings [67][68][69][70][71][72]. To combat such misconceptions, various studies have developed approaches such as CFD instrumentation, e-learning, experimental hands-on implementation, interview analyses, student engagement, and interactive learning techniques, among others [73][74][75][76][77][78][79][80].…”
Section: Work In Progress In Learning and Teaching Fluid Mechanicsmentioning
confidence: 99%
“…In fluid mechanics, literature on teaching, formative assessment, remedial instruction, and tools are expanding much more than excepted. It has been reported that concepts from pressure and fluid statics [57,[60][61][62][63][64][65], to Archimedes' principle [66], to Bernoulli's law often lead to misunderstandings [67][68][69][70][71][72]. To combat such misconceptions, various studies have developed approaches such as CFD instrumentation, e-learning, experimental hands-on implementation, interview analyses, student engagement, and interactive learning techniques, among others [73][74][75][76][77][78][79][80].…”
Section: Work In Progress In Learning and Teaching Fluid Mechanicsmentioning
confidence: 99%
“…Various proposals have been tabled on distance experimental teaching [1][2][3][4][5], while various researchers have attempted to investigate the effectiveness of the approaches proposed, some of them speculating in favour of the virtual version of teaching than the lives ones [6][7][8]. In this context, we filmed more than 65 experiments [9], narrated in Greek, to be used in distance learning to enhance students' data processing skills and highlight the trustworthiness of the experimental data in conducting accurate predictions.…”
Section: Introductionmentioning
confidence: 99%